Transforming the Chemistry Education Curriculum: Students’ Creativity Using AI in Lectures - Farwati, Ratna; Sari, Indah; Fadhilah, Geby Ayu (Universitas Pendidikan Mandalika, 2024)
This Research examines of The Usage of Artificial Intelligence (AI) such as ChatGPT and alike of that by Chemistry Education students in the learning process, and provides recommendations for the transformation of the chemistry education curriculum. The results of a survey of 76 students from universities in Palembang and Serang show that ChatGPT and similar AI have become important tools in supporting academic activities, especially in understanding chemistry concepts, compiling reports, and conducting research. However, students face several problems, including the cost of use, lack of knowledge about AI, limited access, and operational difficulties. Therefore, this study recommends the integration of AI into lecture materials, the provision of comprehensive training, increasing access and technical support, and periodic evaluation and adjustment of the curriculum.